A Guide to Classics and Cognitive Studies Reviewing findings and results - Novokhatko, Anna A. 1978- (De Gruyter, 2024)
Readers of this book receive an overview of the main perspectives and research of recent decades in the fruitful collaboration between Classics and Cognitive studies. It is intended as a stocktaking of various branches of Classics, such as literary criticism and poetics, linguistics, ancient history and archaeology. Four major research areas or clusters have been chosen for the presentation of the chapters. Chapter one discusses recent studies of 'cognitive' materiality and material agency in relation to the human mind, chapter two the so-called 'spatial turn' and cognition and the perception of space in place in relation to antiquity, chapter three imagination and vision and cognitive approaches to seeing, while chapter four considers experience and experientiality and the 'sensory turn' as applied to ancient sources. Finally, the fifth chapter is a special case and a different medium: it consists of three interviews with three well-known pioneers of the study of emotions in antiquity, David Konstan, Angelos Chaniotis and Douglas Cairns, who in various direct and indirect ways have greatly influenced the interplay and dialogue between classical studies and cognitive approaches in recent decades. This book takes stock of a rapidly developing and highly controversial field that is currently in full bloom